2020
DOI: 10.3390/ijerph17082824
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox Association between Smoking and Blood Pressure among Half Million Chinese People

Abstract: Background: The association between smoking and blood pressure (BP) has been explored extensively, yet the results remain inconclusive. Using real-world evidence of a large Chinese population, we examine the effect of smoking on BP levels. Methods: We utilize half a million adults from the China Kadoorie Biobank (CKB) study with baseline sampling collected between 2004 and 2008. Multivariable linear regression analyses are used to estimate linear regression coefficients of smoking for systolic blood pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
(50 reference statements)
5
24
0
Order By: Relevance
“…Compared with an average dairy products intake of ~118.22 g/d in our study, the mean intake of dairy products in the United States was much higher, ~268.8 g/day ( 27 ). It is important to note that smokers have accounted for nearly 50% of all participants, this percent is close to a previous study from the China Kadoorie Biobank project, smokers aged between 30 and 69 accounted for more than 50% ( 28 ).…”
Section: Discussionsupporting
confidence: 84%
“…Compared with an average dairy products intake of ~118.22 g/d in our study, the mean intake of dairy products in the United States was much higher, ~268.8 g/day ( 27 ). It is important to note that smokers have accounted for nearly 50% of all participants, this percent is close to a previous study from the China Kadoorie Biobank project, smokers aged between 30 and 69 accounted for more than 50% ( 28 ).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, smokers tend to consume more alcohol than non-smokers, which leads to a higher risk of hypertension than in non-smokers. The finding that alcohol consumption, especially heavy drinking, was more strongly associated with hypertension risk in smokers than in non-smokers were consistent with several previous reports [ 42 , 45 , 46 ]. However, this association remains controversial.…”
Section: Discussionsupporting
confidence: 93%
“…Smokers were also at an increased odds of drinking alcohol irrespective of gender [ 23 , 25 , 28 ]. Additionally, smoking and drinking concurrently also elevated the risk of hypertension [ 29 , 30 ]. Another study found that the proportion of smokers among drinkers was high [ 30 ], which was also consistent with our study findings where the prevalence of smokers among current drinkers was 19.2%.…”
Section: Discussionmentioning
confidence: 99%